Determinant of Zakat Compliance Intention Among Self-Employed Income Earners in Kubang Pasu and Kota Star - Mohmad Zaki, Othman (2008)
An increase in the number of small and medium enterprise (SMEs) in Kubang Pasu and Kota Star means that more self-employed income earners could be targeted as potential zakat payers on income. Hence, the present study sought to examine compliance behaviour among this group of people toward zakat on self-employed income. In particular, this study examines the relationship between attitude, subjective norm and perceived behaviour control on zakat compliance intention among self-employed income earners in Kubang Pasu and Kota Star based on Theory of Planned Behaviour (TBP). A sample of 115 self-employed income earners in Kubang Pasu and Kota Star completed questionnaires consisting of 15 items measuring attitude (ATT), subjective norm (SN), perceived behaviour control (PBC) and intention (ITT) to pay zakat on self-employment income. The finding of the study shows that attitude (ATT) and perceived behaviour control (PBC) significantly influence intention to comply with zakat on income. Subjective norm (SN), however, did not show any significant influence on zakat compliance. In general, however, the study reveals that the TBP model is capable to predict zakat compliance intention, which can be used to explain zakat compliance behaviour in the future. The implications of the present study to the institution of zakat and policy makers, and to future research are discussed further in this study. In addition, the study’s limitations are also discussed.